The Mediation Effect of Hyperarousal Symptoms on the Relationship Between Childhood Physical Abuse and Suicidal Ideation of Patients With PTSD - Kwon, Aeran; Lee, Hyun Seo; Lee, Seung-Hwan (Frontiers in Psychiatry, 2021)
Objective: This study examined the relationship of childhood physical abuse, posttraumatic stress disorder (PTSD), depression, and suicide in patients with PTSD through path analysis. Materials and Methods: A total of 114 patients with PTSD (36 men and 78 women) were recruited and completed psychological assessments including the Childhood Trauma Questionnaire, the scale for suicidal ideation, the clinician-administered PTSD scale for the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition, the PTSD checklist, and the Hospital Anxiety and Depression Scale. Structural equation modeling was used to evaluate the results. We developed a model including childhood physical abuse experience as the causal variable, suicidal ideation as a result variable, and PTSD and depression as mediation variables. PTSD symptoms were divided into four clusters [intrusion, avoidance, negative cognition and mood, and altered arousal and reactivity (hyperarousal)] to determine predictive power for suicide. Results: PTSD symptoms fully mediated the relationship between childhood physical abuse and suicidal ideation. Furthermore, PTSD symptoms fully mediated the relationship between childhood physical abuse and depression. Among the PTSD symptoms, hyperarousal was the only symptom cluster that mediated the relationship between childhood physical abuse and suicidal ideation. The symptom clusters of negative cognition and mood as well as hyperarousal mediated the relationship between childhood physical abuse and depression. Conclusions: This study presents a link between childhood physical abuse and current symptoms in patients with PTSD, and highlights specific PTSD symptom clusters (i.e., hyperarousal, negative cognition and mood) that may increase the risk for psychopathology later in life.